U.S. College Student Media and Twitter: Are Student Media Following Best Practices?. (September 2019) - Saks, Jeremy; Cruikshank, Sally Ann; Yanity, Molly
The current study examines how student media in the United States utilize Twitter and if those media outlets are following best practices. A constructed-sample content analysis of 10 Twitter feeds over the course of four semesters was conducted. The findings show that student media are generally not following best practices with a wide range of differences among those outlets in the sample. Discussion includes what this means for institutions teaching social media for journalists and other concerns.